Optimizing customer experience with CJM in practice - Otarbayeva, Marzhan; Luc, Ladislav; Yessengaliyeva, Aigerim; Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky (2025)
The aim of this thesis is to develop recommendations for improving the customer experience in a Kazakhstani fintech company using specialized tools to perform the following tasks: analysis of service design methodology, creation of a customer experience map, building a structured information model of this map, analysis of customer experience data, identification of problems that hinder its improvement, and determination of possible solutions to these problems. The thesis consists of two main parts. The first, theoretical part, includes an explanation of the concept of customer experience, an overview of approaches to service design, a description of the elements of a customer journey map (CJM), the methodology and principles of customer relationship management, and a justification of the need for visual modelling of customer experience. The second, practical part, conducted within the framework of a Kazakhstani payment integrator (a company providing payment services), is devoted to establishing the current state of customer experience, identifying bottlenecks in the customer experience and customer service departments. To this end, methods of customer data analysis from various sources (ABC analysis of CRM data, customer survey, and interview analysis, hypothesis testing, touchpoint evaluation analysis) are used to identify factors negatively affecting customer experience and suggest ways to improve it.
Vedoucí práce: Ladislav Luc
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: informační management [obor dipl. práce]; diplomové práce; master's theses